Kompetensi Guru Memanfaatkan Teknologi Informasi dan Komunikasi dalam Mengembangkan Media Pembelajaran Online - Ucup Supriatna (Universitas Muhammadiyah Enrekang, 2021)
The impact of the Covid-19 pandemic that has hit the whole world, including in Indonesia, has forced teachers to transform learning from face-to-face to online learning by utilizing information and communication technology in a short time with various limitations including limited internet access, teacher competence, and student readiness. This study aims to reveal how the competence of teachers in using information and communication technology to develop online learning media so that online learning can be carried out effectively. This research is qualitative research with a survey method. The results of the study concluded that teachers have the competence to use information and communication technology in developing online learning media but need to increase competence in developing online learning media using information and communication technology based on the stages of media development and following instructional design patterns.